Histoire d'un quartier de Montbéliard (Doubs) Le bourg Saint-Martin (XIIIe-XXe s.) - Cantrelle, Sylvie; Goy, Corinne; Munier, Claudine (Documents d'archéologie française, 2000)
The history of Montbeliard began in the late 9th century with the construction of a castle on a rocky spur overlooking the Allan and the Lizaine rivers. The city developed as a result of contact with both Burgundian and Germanic culture and by the end of the 14th century had become a commercial and religious centre. The second defensive wall, built in the 15th century is a reflection of the city's prosperity, encircling as it does the original castle, through as well as the two districts of La Halle and Saint-Martin. Excavation work undertaken in 1993-1994 prior to the construction of a shopping centre in the Velotte quarter of the Saint-Martin district has enabled archeologists to define seven build periods of architectural development covering both buildings and the urban defense system. This work has also shed light on various aspects of daily and social life as experienced by the inhabitants of this area within the city walls the bucolic character of which remained intact up to the final quarter of the 19th century.